ANALISIS EFEKTIVITAS PENYELENGGARAAN PELAYANAN DMINISTRASI TERPADU KECAMATAN GUGUK PANJANG KOTA BUKITTINGGI DALAM PERSPEKTIF EKONOMI PUBLIK - Rayuni Rayuni (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to examine and analyze the effectiveness of the Integrated Subdistrict Administrative Services (PATEN) in Guguk Panjang District, Bukittinggi City, within a public economics framework. PATEN is a public service innovation focused on simplifying procedures, increasing legal certainty, and saving time and money in resolving public administrative matters. The research method used was descriptive qualitative, with data collection techniques including field observations, in-depth interviews with officials and service users, and analysis of related documents. The results revealed that the implementation of PATEN in Guguk Panjang District has generally been quite effective, as reflected in the increased speed of service, affordability, and level of public satisfaction with the services provided. However, service effectiveness still faces several obstacles, including limitations in the number and competence of human resources, the availability of infrastructure, and the suboptimal use of information technology. From a public economics perspective, the effectiveness of integrated administrative services has implications for efficient resource allocation, reduced transaction costs borne by the public, and increased public trust in local government officials. Furthermore, effective service delivery contributes to the local economic climate by streamlining public administration, which in turn stimulates broader economic activity. Therefore, strategic steps are needed to improve the capacity of government officials, modernize technology-based service systems, and strengthen transparent and accountable governance to achieve responsive, efficient, and sustainable public services.